2000
DOI: 10.1073/pnas.98.1.60
|View full text |Cite
|
Sign up to set email alerts
|

An anthelmintic compound, nafuredin, shows selective inhibition of complex I in helminth mitochondria

Abstract: Infections with parasitic helminths are important causes of morbidity and mortality worldwide. New drugs that are parasite specific and minimally toxic to the host are needed to counter these infections effectively. Here we report the finding of a previously unidentified compound, nafuredin, from Aspergillus niger. Nafuredin inhibits NADH-fumarate reductase (complexes I ؉ II) activity, a unique anaerobic electron transport system in helminth mitochondria, at nM order. It competes for the quinone-binding site i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(46 citation statements)
references
References 24 publications
(2 reference statements)
0
44
0
Order By: Relevance
“…SQR activity was measured in the presence of 2,3-dimethoxy-5-methyl-6-geranyl-1,4-benzoquinone (UQ 2 ) and 2,6-dichlorophenolindophenol (DCIP) (28). Rhodoquinolfumarate reductase and NADH-fumarate reductase activities were measured under anaerobic conditions (22). NADHcytochrome c reductase activity was measured as described (29).…”
Section: Fermentation and Purification Of Harzianopyridone And Atpeninsmentioning
confidence: 99%
See 1 more Smart Citation
“…SQR activity was measured in the presence of 2,3-dimethoxy-5-methyl-6-geranyl-1,4-benzoquinone (UQ 2 ) and 2,6-dichlorophenolindophenol (DCIP) (28). Rhodoquinolfumarate reductase and NADH-fumarate reductase activities were measured under anaerobic conditions (22). NADHcytochrome c reductase activity was measured as described (29).…”
Section: Fermentation and Purification Of Harzianopyridone And Atpeninsmentioning
confidence: 99%
“…In the course of screening microbial broths for inhibitors of the NADH-fumarate pathway, we isolated a previously uncharacterized compound, nafuredin (20,21). We determined that nafuredin is a selective inhibitor of helminth complex I (NADH-quinone oxidoreductase), and was an effective antihelmintic in animal trials (22). Further screening for inhibitors led to the isolation of harzianopyridone, an inhibitor of the NADH-fumarate reductase activity of adult Ascaris suum mitochondria.…”
mentioning
confidence: 99%
“…1 H and 13 C NMR spectra were obtained using Agilent Technologies Mercury-300 and UNITY-400 spectrometers, and chemical shifts were reported on the d scale based on internal TMS. MS spectra were measured with JEOL JMS-AX505HA, JMS-700 MStation, and JEOL JMS-T100LP spectrometers.…”
Section: Generalmentioning
confidence: 99%
“…In addition, 1 demonstrated anthelmintic activity against Haemonchus contortus in in vivo trials with sheep. 1 Therefore, nafuredin (1) holds promise as a selective antiparasitic agent. A subsequent total synthetic study of 1 identified a novel and structurally simpler c-lactone compound, nafuredin-c (2), which was generated from 1 under mild basic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Different categories of bioactive metabolites were retrieved from those marine fungi with polyketides (40% of 690 structures), alkaloids (20%), peptides (15%), terpenoids (15%), prenylated polyketides (7%), shikimates (2%), and lipids (1%). Polyketides from marine fungi showed different types of activity, including: (i) anthelmintic compounds, such as nafuredin, from Aspergillus niger isolated from sponges ( Omura et al, 2001); (ii) anticancer compounds, such as chaetomugilins, leptosphaerone C or penicillenone isolated from Chaetomium globosum and Penicillium sp. isolated respectively from marine fishes and mangrove plants (Lin et al, 2008;Yamada, Muroga, and Tanaka, 2009); (iii) antimicrobial compounds with ascochyatin obtained from Ascochyta sp.…”
Section: Biotechnological Potentialmentioning
confidence: 99%